Intentional polymedicamentose poisoning with psychotropic drugs – case report - Ždrale, Branislava; Repić, Aleksandra; Pavlekić, Snežana; Alempijević, Djordje; Lukić, Vera (Archives of Pharmacy, 2022)
Antidepressants, antipsychotics and anxiolytics are drugs prescribed as monotherapy or polimedicamentose treatment of depression, schizophrenia, bipolar and sleep disorders. Therapy in these patients carries an additional risk of suicide with prescription drugs. Laboratory of toxicology of the Institute of Forensic Medicine has received the postmortem samples of blood, urine, and vitreous humour of a 41-year-old woman with a presumption that death has occurred due to drug poisoning. Samples were prepared by liquid-liquid extraction, evaporated to dryness, reconstituited in methanol and analyzed by liquid chromatography with tandem mass spectrometry. It was used Xterra columne C18 (3.5um, 4.6 x 100mm). Methanol and 0.1% formic acid in water (flow rate 0.4 mL/min) were used as the mobile phase. Antipsychotic drug, quetiapine, antidepressants (clomipramine, mirtazapine), benzodiazepines (diazepam, nordiazepam, 7-aminoclonazepam) and hypnotic drug, zolpidem, have been detected in all analyzed samples. Identification of quetiapine and clomipramine was accomplished using the ion transitions m/z 384.0 → 253.0 and 221.15 and m/z 314.75 → 86.15 and 58.15, respectively. Quetiapine and clomipramine were detected in lethal concentrations in blood (13.82 mg/L and 2.51 mg/L). Other detected drugs were within therapeutic range. Significant concentrations of all detected drugs were observed in urine and vitreous humor. Given the fact that antipsychotics follow the postmortem redistribution process it is hard to conclude that quetiapine is the main reason of the lethal outcome. Based on the autopsy findings, pathohistological examination and chemical-toxicological analysis, it was concluded that the death was violent and occurred due to combined drugs poisoning.